The presence of a second obstacle in the obstacle avoidance task changes the locomotor pattern of older adults at lower and higher risk of falling. - MAGALHÃES, GABRIELA V.; CORREA, MARIA E. M.; SILVA, JULIANA A.; RAZUK, MILENA; RINALDI, NATALIA M. (Brazilian Journal of Motor Behavior, 2025)
BACKGROUND: The literature does not fully explain how the sequenced addition of a second obstacle during walking influences the avoidance task in older adults at lower and higher risk of falling. AIM: The objective was investigating the locomotor performance of older adults at higher and lower risk of falling during sequenced obstacles avoidance with different physical characteristics. METHODS: 10 older adults at higher risk of falling and 11 older adults at lower risk of falling participated in this study and performed the following tasks: 1) single obstacle avoidance and 2) double obstacle avoidance. For both conditions, the physical characteristics of the obstacles were manipulated: solid (a single piece of foam) and fragile (foam blocks stacked) obstacles were used. RESULTS: Older adults at higher risk of falling, when compared to older adults at lower risk of falling, showed longer right stride duration (1.261s | 1.030s, respectively; p≤0.001), longer left stride duration (1.409s | 1.073s, p≤0.001), and lower left stride velocity (0.866 cm/s | 1.130 cm/s, p=0.013). They also showed a longer avoidance time (0.772s | 0.635s, p=0.009), and lower toe clearance (0.327 cm | 0.380 cm, p=0.037) and obstacle-heel horizontal distance (0.651 cm | 0.798 cm, p=0.025). INTERPRETATION: Older adults at higher risk of falling showed changes in locomotor pattern when avoidance obstacles when they were subjected to a more challenging task. These results enable the development of targeted approaches for the rehabilitation of older adults at higher risk of falling and for the prevention of falls.